Undrained shear strength of saturated cohesive soils depending on consolidation pressure and mineralogical properties - Dolinar, Bojana (Acta geotechnica Slovenica, 2004)
The relationship between the water content and the undrained shear strength of finely grained soils can be described with a nonlinear function in which the type of soils is determined by two parameters. These parameters depend primarily on the size of clay minerals, their quantity in soil composition and the interlayer water quantity in expanding clay minerals. This article asserts that there exists also the exactly defined relationship also between the water content and consolidation pressure. In the function describing this relationship, the type of soil is determined by two parameters. They can be expressed depending on the same mineralogical properties of soils as the values of parameters in the function showing the relationship between the water content and the undrained shear strength. These findings allow us to express the ratio between undrained shear strength and consolidation pressure depending on mineralogical properties of soils.
Keywords: geomehanika; gline; lastnosti tal; specifična površina; stisljivost; strižna trdnost